PACITAN BATIK: CONTINUITY AND CHANGES - Nanang Setiyoko (Universitas Gadjah Mada, 2022)
The main objective of this research is to explore and observe the existence, development, and changes of Pacitan batik, especially in the aspect of form, function and product of Pacitan batik in social, cultural and economic contexts. This research is descriptive qualitative by using a multidisciplinary approach, culture, aesthetics in the hope that it can answer all the problems. Changes caused by internal factors can occur due to new interpretations and perceptions of the Pacitan community, as a community that supports batik cloth. Pacitan people have a sense to participate in the development, innovation, ideas, and new creations of Pacitan batik. Changes caused by external factors generally occur because of relationships, communication, and social and cultural interactions with other cultures. Pacitan batik products have also experienced developments and changes, both in quantity and quality. Broadly speaking, the changes that occurred in Pacitan batik were marked by a change in its function, from the beginning as a long cloth worn by women during official events or during celebrations, to now becoming a trade commodity product. The motifs applied to Pacitan batik initially contained deep philosophical symbolic meanings, but now these meanings have been put aside, and only evaluated for their aesthetic aspects. Changes in cultural products will have an impact on the supporting community, both in terms of socio-cultural aspects, as well as socio-economic aspects.